IMPLEMENTATION OF MODERNIZATION AND DIVERSIFICATION PROCESSES IN NATIONAL COMPANIES - AhmedovIkromAkramovich (The journal of contemporary issues in business and government, 2021)
This article explores the concepts of diversification and modernization and the factors that influence them. Particular attention is paid to the comprehensive analysis of these concepts, the study of their essence from the point of view of representatives of the classical school and neoclassicists. Methods for assessing the competitiveness of an enterprise are analyzed. The influence of diversification, modernization and innovation factors affecting competitiveness is analyzed, their importance for increasing the country’s export potential is revealed.